(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2025)
The paper gives useful information about how workers of the hotel industry perceive various areas of family support, workplace support, social support, working environment, and work-life balance. The findings highlight the interplay of these variables and their combined impact on workers’ work satisfaction and overall well-being. Hence, the paper has taken 190 hotel workers from three 4-stars hotels operating within Dhulikhel municipality to collect opinions on work-life balance among the workers of the hospitality industry. The study found that family support plays a vital role among the variables of work-life balance in the context to hospitality industry. Similarly, the paper found a neutral to somewhat favourable opinion of society attitudes towards employment, with potential for increased appreciation, recognition, and support within the community. The paper also concluded that the working environment has a very strong impact on work-life balance among the workers.